Try NerdPal: our new app on iOS and Android !

Simplify the expression $\frac{x^3+x-1}{x^4+6x^2+9}$

Related Videos

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Algebra 2 - Simplify by dividing two rational expressions using factoring (32/n‐8)/(1/n‐8)

https://www.youtube.com/watch?v=wFy0p8Jo6pQ

Using long division to divide polynomials - Math tutorial

https://www.youtube.com/watch?v=Ew1eMrKMVeA

Algebra 2 - Learn how to divide using long division with multiple zeros, (x^5 - 1) / (x - 1)

https://www.youtube.com/watch?v=QLmbtmqii9o

Simplifying rational expressions 1 | Polynomial and rational functions | Algebra II | Khan Academy

https://www.youtube.com/watch?v=XChok8XlF90

Dividing polynomials by linear expressions | Algebra 2 | Khan Academy

https://www.youtube.com/watch?v=G2VBRwXq1q4

Use Synthetic Division to Find the Remaining Zeros Given One Imaginary Zero

https://www.youtube.com/watch?v=bezXsXqw_5s
SnapXam A2
Answer Assistant

beta
Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Tips on how to improve your answer:

$\frac{x^3+x-1}{x^4+6x^2+9}$

Time to solve it:

~ 0.05 s